Effects of structural complexity and habitat type on the gall distribution of Jatrophobia brasiliensis (Rübsaamen, 1907) (Diptera, Cecidomyiidae) in two host-species of Manihot (Euphorbiaceae) - Scarcela, Mariane D. (2020)
In the present study, we evaluate the distribution of galls induced by Jatrophobia brasiliensis (Rübsaamen, 1907) in two species of Manihot (Manihot caerulescens Pohl and Manihot sp.). The study was performed in two Cerrado phytophysiognomies (typical savannah and rocky savannah) in Jequitaí municipality, Minas Gerais, Brazil. A total of 1,157 galls of Jatrophobia brasiliensis were analyzed, of which 459 galls in Manihot sp. and 698 galls in Manihot caerulescens. We found that plant height, crown diameter and number of leaves per branch positively influenced the number of galled leaves. Our results also showed that habitat type influenced the number of galled leaves and the gall size, with the rocky savannah presenting more and larger galls than the typical savannah. Our findings demonstrate that both intrinsic (related to host plant structure) and extrinsic factors (related to habitat type) influence the distribution of the galls induced by Jatrophobia brasiliensis on Manihot.